Safety and efficacy of remote ischemic conditioning in adult moyamoya disease patients undergoing revascularization surgery: a pilot study - Heng Yang; Heng Yang; Heng Yang; Heng Yang; Heng Yang; Zhenzhen Hu; Xinjie Gao; Xinjie Gao; Xinjie Gao; Xinjie Gao; Xinjie Gao; Jiabin Su; et al. (Frontiers in Neurology, 2023)
Background and purposeRevascularization surgery for patients with moyamoya disease (MMD) is very complicated and has a high rate of postoperative complications. This pilot study aimed to prove the safety and efficacy of remote ischemic conditioning (RIC) in adult MMD patients undergoing revascularization surgery.MethodsA total of 44 patients with MMD were enrolled in this single-center, open-label, prospective, parallel randomized study, including 22 patients assigned to the sham group and 22 patients assigned to the RIC group. The primary outcome was the incidence of major neurologic complications during the perioperative period. Secondary outcomes were the modified Rankin Scale (mRS) score at discharge, at 90 days post-operation, and at 1 year after the operation. The outcome of safety was the incidence of adverse events associated with RIC. Blood samples were obtained to monitor the serum concentrations of cytokines (VEGF, IL-6).ResultsNo subjects experienced adverse events during RIC intervention, and all patients could tolerate the RIC intervention in the perioperative period. The incidence of major neurologic complications was significantly lower in the RIC group compared with the control group (18.2% vs. 54.5%, P = 0.027). The mRS score at discharge in the RIC group was also lower than the control group (0.86 ± 0.99 vs. 1.18 ± 1.22, P = 0.035). In addition, the serum IL-6 level increased significantly at 7 days after bypass surgery in the control group and the serum level of VEGF at 7 days post-operation in the RIC group.ConclusionIn conclusion, our study demonstrated the neuroprotective effect of RIC by reducing perioperative complications and improving cerebral blood flow in adult MMD patients undergoing revascularization surgery. Thus, RIC seems to be a potential treatment method for MMD.Clinical trial registrationClinicalTrials.gov, identifier: NCT05860946.